Analisis Kebiasaan Belajar Siswa Terhadap Prestasi Belajar IPS di Kelas V SDN 04 Singkawang - Nur hidayah Nurhidayah; Tamia Triyanti; Mertika Mertika; Emi Sulistri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the student's study habits on social studies learning achievement in class V SDN 04 Singkawang Tengah. In this study, the subjects used were 5 subjects who were able to provide the data that the researchers wanted. Data collection techniques used are observation, interviews, and documentation. The results of this study show that students' learning habits on social studies learning achievement in class V SDN 04 Singkawang Tengah have something to do with indicators of study habits, namely: the first indicator, there are 60% of these students have read and made notes well, so that the achievements achieved by category/criteria well, this is evidenced from the results of student and teacher interviews, and further strengthened by the value of student report cards with grades 1-3. The second indicator, 100% of these students do not concentrate in learning, so the results achieved with the category/criteria are not good. This can be seen from the value of student report cards with grades 1-5. The last indicator is that 60% of these students have done their assignments well, and their learning achievements are in good categories/criteria, this can be proven from the results of student and teacher interviews, as well as reinforced by student report cards grades 1-3. Thus, it can be concluded that students' study habits towards social studies learning achievement are good. Keywords: Study habits, learning achievement, Social.